Using multimedia computer-assisted language learning to promote oral interaction for Chinese learners. (1st January 2014) - Jiang, Yaoyi; Guan, Lin
An extensive body of research has established the efficacy of computer-assisted language learning (CALL) in developing interaction in the field of language education. Aiming to offer Chinese English-as-a-foreign-language (EFL) teachers more detailed implication and guidance in promoting oral interaction of learners, this study examined and evaluated the correlation between interaction modes and multimedia tasks. The results show that there was no one-one correlation between the tasks types and the interaction modes, but the task types did affect the quality of interaction. The participants were also generally positive towards the CALL tasks. This paper presents the design of the study and its major findings. Implications for instructional design of CALL tasks to promote oral interaction are proposed.